Peran Guru Dalam Menstimulasi Perkembangan Kognitif Anak Usia 5-6 Tahun di TK Idhata Pontianak - Tiwi Okta Rini; Sudarti Sudarti; Yuniarti Yuniarti (Jurnal Ilmiah Cahaya Paud, 2026)
This research was motivated by the importance of the teacher’s role in stimulating the cognitive development of early childhood, especially children aged 5–6 years. Cognitive development is the ability to think, understand, solve problems, and develop knowledge that needs to be optimally stimulated from an early age. Teachers have an important role as educators, mentors, and evaluators in supporting children’s cognitive development in the school environment. This study aims to describe the role of teachers as educators, mentors, and evaluators in stimulating the cognitive development of children aged 5–6 years at TK Idhata Pontianak. The research method used was descriptive qualitative research. The subjects of this study consisted of the principal, teachers, and students at TK Idhata Pontianak. Data collection techniques were carried out through observation, interviews, and documentation. The results of the study showed that teachers actively played a role in stimulating children’s cognitive development through interesting learning activities, the use of varied learning media, providing guidance to children, and conducting periodic evaluations of children’s development. Teachers also implemented the Merdeka Curriculum, which is child-centered, enabling children to think critically, express their opinions confidently, and actively participate in the learning process. Therefore, the role of teachers is very important in supporting the optimal cognitive development of early childhood.